The Wounded Healer: A Phenomenological Study on Hospital Nurses Who Contracted COVID-19 - Michela Piredda; Jacopo Fiorini; Anna Marchetti; Chiara Mastroianni; Beatrice Albanesi; Lucilla Livigni; Gemma Carrabs; Francesco Zaghini; Maria Grazia De Marinis; Alessandro Sili (Frontiers Media S.A., 2022)
Since the pandemic began nurses were at the forefront of the crisis, assisting countless COVID-19 patients, facing unpreparedness, social and family isolation, and lack of protective equipment. Of all health professionals, nurses were those most frequently infected. Research on healthcare professionals' experience of the pandemic and how it may have influenced their life and work is sparse. No study has focused on the experiences of nurses who contracted COVID-19 and afterwards returned to caring for patients with COVID-19. The purpose of this study was therefore to explore the lived personal and professional experiences of such nurses, and to describe the impact it had on their ways of approaching patients, caring for them, and practicing their profession. A phenomenological study was conducted with 54 nurses, through 20 individual interviews and 4 focus groups. The main finding is that the nurses who contracted COVID-19 became "wounded healers": they survived and recovered, but remained "wounded" by the experience, and returned to caring for patients as "healers," with increased compassion and attention to basic needs. Through this life-changing experience they strengthened their ability to build therapeutic relationships with patients and re-discovered fundamental values of nursing. These are some of the ways in which nurses can express most profoundly the ethics of work done well.